The efficient degradation and mechanism of sulfamethoxazole using ZnO/ZnIn2S4 heterojunction under visible light - Gan, Xinhong; Song, Yang; Liu, Guoqiang; Zhang, Huijuan; Yang, Jianhua (Frontiers in Environmental Science, 2023)
We hydrothermally synthesized a flower-shaped ZnO/ZnIn2S4(ZnO/ZIS) Z-scheme heterojunction, which could decompose antibiotics efficiently. Meanwhile, the photocatalysts degradation of sulfamethoxazole (SMX) as the representative pollutant by ZnO/ZIS were studied deeply. When irradiated by a xenon lamp (500 W), ZnO/ZIS (0.20 g/L) degraded SMX (2.5 mg/L) in 6.5 h with an efficiency of 74.9%. The •O2 -and h + played key roles in the visible light-assisted decomposition of SMX by ZnO/ZIS, while the role of •OH was supplementary. Additionally, we investigated the mechanism of the generation of active species environmentally persistent free radicals (PFRs) within the SMX degradation using ZnO/ZIS by performing computations and experimental analyses based on density functional theory. Besides, PFRs (predominantly oxygen-centered) generated during the visible light-assisted SMX degradation by ZnO/ZIS had a concentration of 10 11 spin/mm 3 . The generation of PFRs involves two major events, i.e., chemical adsorption and electron transfer. To adsorb the precursor F9a on ZnO, the energy required was -2.03 eV, and the electrons were transferred to the ZnO/ZnIn2S4 heterojunction from the precursor F9a. The PFRs only had minor negative impacts on the SMX degradation through ZnO/ZIS.